Between ethics and existentialism: placing film communities - Abu Hassan, Badrul Redzuan; Abdul Latif, Roslina; Yaakup, Hani Salwah; Selvaraj, Madhumita (Taylor's University, 2023)
Generally, film communities around the world are perceived to be sharing the singular purpose of showing films outside of cinema theatres. Film screening by non-profits is increasingly a social practice that is gaining traction as part of the globalized but independent “Do-It-Yourself” cultural movement comprising and undertaken by a plethora of agentive, social citizens: cineastes, filmmakers, and enthusiasts. Film communities may be seen as part of cultural “modernity” as they generally emerged well after a national film industry’s exhibition and distribution chains have been established. As such, film communities should not be considered a bane to any local industry in any competitive respect. They are peripheral, if not invisible to market forces and the marketplace. Nonetheless, a film community may have its own moral codes of conduct and rationale for its presence in the society.